Information warfare and electronic warfare systems - Poisel, Richard A. (Artech House, 2013)
This book is the first in the field to address communication electronic warfare EW systems in the context of information warfare. The book includes a unique formulation of EW system performance and presents results of system simulations that have not appeared previously in any related literature.